Long-term follow-up of biomarkers of vascular calcification after switch from traditional hemodialysis to online hemodiafiltration. (3rd April 2019) - Uhlin, Fredrik; Fernström, Anders; Knapen, Marjo H. J.; Vermeer, Cees; Magnusson, Per
Abstract: Rapid progression of vascular calcification (VC) in hemodialysis (HD) patients is caused by several factors including inflammation and an imbalance between active inducers and inhibitors of VC. Growing evidence shows that online hemodiafiltration (ol-HDF), a combination of diffusive and convective solute transport, has positive effects on the uremic environment that affects patients on dialysis. However, we recently reported that serum 25-hydroxyvitamin D (25(OH)D) decreased after a switch from HD to ol-HDF. As a consequence of this finding, the present study was undertaken to investigate if inducers and inhibitors of VC (i.e. the inactive matrix Gla protein fractions dp-ucMGP and t-ucMGP, fetuin-A, Gla-rich protein (GRP), osteopontin (OPN), bone-specific alkaline phosphatase (BALP), and osteoprotegerin (OPG)) also are affected by ol-HDF. This non-comparative prospective study comprised 35 prevalent patients who were investigated 6, 12, and 24 months after their switch from HD to ol-HDF. Most patients had increased levels of the calcification inhibitors OPN and OPG; and of the inactive calcification inhibitor dp-ucMGP during the study period irrespective of the dialysis modality. BALP and t-ucMGP were mostly within the reference interval, but fetuin-A was mostly below the reference interval during the study period. OPN was significantly associated with BALP and parathyroid hormone, r  = 0.62 and r  = 0.65 ( p  < .001), respectively. In conclusion, in contrast to decreased 25(OH)D levels, no differences were found for any of the measured biomarkers of VC following the switch from HD to ol-HDF. Further studies are needed to elucidate how these biomarkers can contribute to calcification risk assessment.